Trace elements in oil shale ashes and waste wood ashes and their leachability with a focus on chromium - Kati Roosalu; Inna Kamenev; Kristel Tanilas; Janek Reinik; Oliver Järvik (Oil Shale, 2025)
In Estonian oil shale power plants, ash is transported to disposal sites using a wet transport method. Due to regional climatic conditions, where annual precipitation exceeds evaporation, part of the recirculated ash transport water has to be periodically discharged into natural surface waters. This discharge practice raises concerns about the potential environmental impact of the discharged water. This paper investigates the leaching behavior of several trace elements from oil shale ash, demolition wood ash, and their mixtures, with a focus on chromium. In particular, the occurrence, mobility, and oxidation state of chromium in the leachate are considered using the example of the mentioned ashes. The possible effect of ash content, influenced by fuel type and the liquid-to-solid (L/S) ratio, on trace element concentrations in the discharged water was studied. In leaching tests with 100% oil shale ash, the chromium concentration in the circulating water increases only slightly when circulating water from the oil shale ash field is used as the leaching medium. On the one hand, the amount of chromium and other trace elements leached from oil shale ash depends on the L/S ratio. At the same time, it is known from the literature that oil shale ash is also capable of binding chromium. The release and concentration of chromium in the leachate increase significantly as the proportion of waste wood ash rises, compared to tests using 100% oil shale ash. Consequently, the concentration of chromium in surface water, depending on the specific ratio of oil shale to waste wood used in co-combustion, can easily exceed the nationally permitted limit value.